The Origin of 8-Amino-3,8-dideoxy-D-manno-octulosonic Acid (Kdo8N) in the Lipopolysaccharide of Shewanella oneidensis - Gattis, Samuel G.; Chung, Hak Suk; Trent, M. Stephen; Raetz, Christian R. H. (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2013)
Lipopolysaccharide (LPS; endotoxin) is an essential component of the outer monolayer of nearly all Gram-negative bacteria. LPS is composed of a hydrophobic anchor, known as lipid A, an inner core oligosaccharide, and a repeating O-antigen polysaccharide. In nearly all species, the first sugar bridging the hydrophobic lipid A and the polysaccharide domain is 3-deoxy-D-manno-octulosonic acid (Kdo), and thus it is critically important for LPS biosynthesis. Modifications to lipid A have been shown to be important for resistance to antimicrobial peptides as well as modulating recognition by the mammalian innate immune system. Therefore, lipid A derivatives have been used for development of vaccine strains and vaccine adjuvants. One derivative that has yet to be studied is 8-amino-3,8-dideoxy-D-manno-octulosonic acid (Kdo8N), which is found exclusively in marine bacteria of the genus Shewanella. Using bioinformatics, a candidate gene cluster for Kdo8N biosynthesis was identified in Shewanella oneidensis. Expression of these genes recombinantly in Escherichia coli resulted in lipid A containing Kdo8N, and in vitro assays confirmed their proposed enzymatic function. Both the in vivo and in vitro data were consistent with direct conversion of Kdo to Kdo8N prior to its incorporation into the Kdo8N-lipid A domain of LPS by a metal-dependent oxidase followed by a glutamate-dependent aminotransferase. To our knowledge, this oxidase is the first enzyme shown to oxidize an alcohol using a metal and molecular oxygen, not NAD(P)(+). Creation of an S. oneidensis in-frame deletion strain showed increased sensitivity to the cationic antimicrobial peptide polymyxin as well as bile salts, suggesting a role in outer membrane integrity.